2022
DOI: 10.3390/ijms23179968
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tryptophan Metabolites in Neuropsychiatric Disorders

Abstract: In recent decades, neuropsychiatric disorders such as major depressive disorder, schizophrenia, bipolar, etc., have become a global health concern, causing various detrimental influences on patients. Tryptophan is an important amino acid that plays an indisputable role in several physiological processes, including neuronal function and immunity. Tryptophan’s metabolism process in the human body occurs using different pathways, including the kynurenine and serotonin pathways. Furthermore, other biologically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 177 publications
0
33
0
3
Order By: Relevance
“…Indoleacetaldehyde plays a pivotal role in the metabolic pathway of tryptophan. Empirical evidence suggests that tryptophan metabolism is implicated in the pathogenesis of depression and hyperactivity in pediatric populations [22][23] . During pregnancy, the metabolism of tryptophan also plays a pivotal role [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Indoleacetaldehyde plays a pivotal role in the metabolic pathway of tryptophan. Empirical evidence suggests that tryptophan metabolism is implicated in the pathogenesis of depression and hyperactivity in pediatric populations [22][23] . During pregnancy, the metabolism of tryptophan also plays a pivotal role [24] .…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with our results indicating changes in lysine, tryptophan, and tyrosine metabolism, all of which can have ketogenic effects. Both the tyrosine and tryptophan pathways have also been linked to neuroin ammation in psychiatric disorders [23,24] and previously associated with AD both in a sex-speci c manner [25,26] and independently of sex [11].…”
Section: Pathway Analysismentioning
confidence: 99%
“…There is a significant increased risk of new mental illness postpartum among women with IBD, specifically in the presence of CD [ 27 ], with the rate of depression and anxiety being highest during active disease states [ 28 ]. Of relevance, it was recently shown that inflammation in the intestines caused by an acute dose of methamphetamine causes leaky gut syndrome, systemic inflammation, inflammation in the brain and mood disorders such as anxiety [ 29 , 30 , 31 ]. Gut inflammation and changes in behaviour are closely related.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%